Tareas extra clase en el proceso de aprendizaje en estudiantes de octavo año de educación general básica sección nocturna del Colegio Nacional en Ciencias Juan Montalvo de Machala, 2013-2014. - Peñaherrera Vásquez, Jefferson Humberto (2016)
This work was done from the perspective deductive hypothetical since it split from a problem and a hypothesis which will be generated work objectives that were developed throughout the investigation. The research is aimed at a school in the city where the problem was the low participation of parents, students did not have access to reliable sources of research so it is very poor presentation of extra clases tasks. Theoretical research to test the theory with reality where research took a tour of the main theories that can help you understand the process of learning took place. The methodology used was to direct research through surveys of participants in the process of teaching and learning, teachers, students and parents, the results were systematized in statistical tables and graphs through which it will proceed to test the hypothesis, coming to conclusions and recommendations to end with an intervention proposal that seeks to solve the problem under study that was originally proposed.